Download presentation

Presentation is loading. Please wait.

Published byStuart Green Modified over 8 years ago

1
Equations – Success if you can do these 3x = 64x + 2 = 3x + 7 x/4 = 25x – 3 = 7 + 3x x + 3 = 173(x + 2) = 12 x – 4 = 134(x + 5) = 32 3x + 4 = 253(2x – 2) = 2(x + 6) 4x – 3 = 174(3x + 5) = 2(x + 15)

2
How to solve the 4(x + 3) = 40 type of equation The 4, 3 and 40 could be any numbers

3
Get rid of the brackets 4(x + 3) = 40

4
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40

5
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40 Subtract 12 from both sides

6
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40 4x + 12 – 12 = 40 – 12 Subtract 12 from both sides

7
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40 4x + 12 – 12 = 40 – 12 4x =28 Subtract 12 from both sides

8
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40 4x + 12 – 12 = 40 – 12 4x =28 Subtract 12 from both sides Divide both sides by 4

9
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40 4x + 12 – 12 = 40 – 12 4x =28 4x/4 = 28/4 Subtract 12 from both sides Divide both sides by 4

10
Get rid of the brackets 4(x + 3) = 40 X x + 3 4 4x + 12 4x + 12 = 40 4x + 12 – 12 = 40 – 12 4x =28 4x/4 = 28/4 = 7 Subtract 12 from both sides Divide both sides by 4

11
Solve this equation 5(x + 2) = 3(x + 10)

12
Get rid of the brackets

13
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 Get rid of the brackets

14
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 5x + 10 –10 = 3x + 30 –10 Get rid of the brackets Subtract 10 from both sides

15
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 5x + 10 –10 = 3x + 30 –10 5x = 3x + 20 Get rid of the brackets Subtract 10 from both sides

16
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 5x + 10 –10 = 3x + 30 –10 5x = 3x + 20 Get rid of the brackets Subtract 10 from both sides Subtract 3x from both sides

17
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 5x + 10 –10 = 3x + 30 –10 5x = 3x + 20 5x – 3x = 3x + 20 –3x 2x = 20 Get rid of the brackets Subtract 10 from both sides Subtract 3x from both sides

18
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 5x + 10 –10 = 3x + 30 –10 5x = 3x + 20 5x – 3x = 3x + 20 –3x 2x = 20 Get rid of the brackets Subtract 10 from both sides Subtract 3x from both sides Divide both sides by 2

19
5(x + 2) = 3(x + 10) 5x + 10 = 3x + 30 5x + 10 –10 = 3x + 30 –10 5x = 3x + 20 5x – 3x = 3x + 20 –3x 2x = 20 2x/2 = 20/2 x = 10 Get rid of the brackets Subtract 10 from both sides Subtract 3x from both sides Divide both sides by 2

20
Remember, always do the same thing to both sides. Felix is checking that you do this properly. 5x + 3 = 43 + 3x 5x + 3 – 3 = 43 – 3 5x = 40 + 3x 5x – 3x = 40 + 3x – 3x 2x = 40 x = 20

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google